The Effect of Hedging Strategy, Exchange Rate Fluctuations, and Credit Risk on the Financial Stability of Multinational Companies in Jakarta - Judijanto, Loso; Kaswoto, Junet; Febrina, Ilza (West Science Social and Humanities Studies, 2025)
This study investigates the impact of hedging strategies, exchange rate fluctuations, and credit risk on the financial stability of multinational companies in Jakarta. Employing a quantitative approach, data were collected from 140 respondents using a Likert scale (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that all three factors significantly influence financial stability, with exchange rate fluctuations exerting the strongest effect, followed by hedging strategies and credit risk. The results underscore the importance of robust financial risk management practices in mitigating external uncertainties and ensuring corporate sustainability. This study offers valuable insights for corporate managers and policymakers in fostering financial resilience amidst volatile market conditions.